Levothyroxine Therapy: Changes of TSH Levels by Switching Patients from Tablet to Liquid Formulation. A Systematic Review and Meta-Analysis - Virili, Camilla; Giovanella, Luca; Fallahi, Poupak; Antonelli, Alessandro; Santaguida, Maria Giulia; Centanni, Marco; Trimboli, Pierpaolo (Frontiers in Endocrinology, 2018)
Background. In the last years, levothyroxine (LT4) has been commercialized also in liquid formulation which is less sensitive to the factors known to reduce the absorption of tablet LT4. To date, there is not robust information that liquid LT4 can improve pharmacologic thyroid homeostasis of patients with reduced efficacy of tablet LT4. This analysis aimed at achieving solid evidence that switching thyroxine treatment from tablet to liquid preparation improves patients’ TSH levels. Methods. The search was performed in PubMed/MEDLINE and Scopus database based on the terms “thyroid”, “levothyroxine” and “liquid”, and updated until September 25, 2017. Studies were included only if they described patients with suboptimal TSH on tablet LT4, subsequently switched to liquid LT4. Results. The literature search retrieved 462 articles and six were finally included. The pooled mean difference of TSH value between tablet and liquid LT4 was 4.23 mIU/L (95%CI from 3.69 to 4.77). Mild heterogeneity was found (I2 60%). Overall mean difference of TSH was significant (p<0.0001). Conclusions. The present meta-analysis showed that patients with suboptimal TSH on tablet LT4 can have a significantly improved TSH by switching to liquid LT4 formulation at unchanged dose.